A high-sensitivity liquid level sensor based on single-mode taper-thin core taper single-mode fiber structure. (9th July 2020) - Shao, Min; Han, Liang; Liang, Junjun; Zhang, Rong; Gao, Hong
Abstract: An optical in-fiber Mach–Zehnder interferometer based on thin core fiber for liquid level sensing is proposed and experimentally demonstrated. The sensor head is composed of a single-mode taper-thin core taper single-mode fiber structure constructed via fusion splicing. The operational principle relies on the sensitivity of intermodal interference to liquid level variation; this is achieved by employing tapers as couplers. Experimental results reveal that the transmission spectrum exhibits a linearly red-shift, with the liquid level changing from 0 to 15 mm, and achieves enhanced sensitivities of 0.6853 nm mm −1, 0.9062 nm mm −1, and 1.2416 nm mm −1 for liquid RIs of 1.3352, 1.3491, and 1.3698, respectively. A temperature assessment is conducted, which demonstrates that the maximum measurement error induced by temperature is −0.017 mm °C −1, which indicates the sensor shows real potential for practical applications.